Efficacy and safety of triple drug fixed-dose combination of telmisartan, amlodipine and hydrochlorothiazide in the management of hypertension - Balraj, Maccha S.; Faruqui, Arif A. (International Journal of Research in Medical Sciences, 2017)
Background: High blood pressure (BP) is the most prevalent chronic disease in India and its prevalence is rapidly increasing among urban and rural populations. This study was conducted to assess the efficacy and safety of triple drug fixed dose combination of Telmisartan 40 mg, Amlodipine 5 mg and Hydrochlorothiazide 12.5mg. Methods: 30 hypertensive patients having systolic blood pressure ≥ 160 mmHg and diastolic blood pressure ≥ 100 mmHg who were uncontrolled on dual drug therapy with Telmisartan-Amlodipine or Telmisartan-Hydrochlorothiazide combinations were enrolled in this study. The treatment period was of 120 days and patients were administered once daily fixed dose combination of Telmisartan 40 mg, Amlodipine 5 mg and Hydrochlorothiazide 12.5 mg. Patients were evaluated on 30th, 60th and 120th days of treatment. Results: There was statistically significant (p<0.0001) decrease in systolic blood pressure from baseline to 30th, 60th and 120th day of treatment mean±SD (157.0±8.68 mmHg vs 148.7±8.19, 137.3±7.84, and 127.0±7.02 mmHg) respectively. Similarly the diastolic blood pressure (DBP) was significantly (p<0.0001) reduced from the baseline to the 30th, 60th and 120th day of treatment (100.0±6.43 mmHg vs. 96.0±6.21, 86.6±6.06 and 80.6±2.53 mmHg respectively). Conclusion: Thus triple drug fixed dose combination of Telmisartan, Amlodipine and hydrochlorothiazide was found to be effective and safe option for the optimal management of hypertension.